The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5039/agraria.v11i2a5372
|View full text |Cite
|
Sign up to set email alerts
|

Repetibilidade das características seminais, espermáticas e fertilidade de garanhões

Abstract: RESUMOO objetivo do presente trabalho foi avaliar a qualidade e estimar a repetibilidade das características físicas e morfológicas do sêmen de garanhões da raça Mangalarga Marchador assim como a fertilidade dos animais durante e fora da estação reprodutiva na região norte do estado do Rio de Janeiro. Foi coletado o sêmen de garanhões da raça Mangalarga Marchador, jovens (≤ 4 anos) e adultos (≥ 5 anos). Foi avaliado o pH, volume seminal, motilidade, vigor, concentração espermática, número total de espermatozoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
0
1
2
Order By: Relevance
“…The mean of seminal volume of the Pantaneiro stallions was similar to the mean(44,4 ± 27,9) observed by Rua et al (2016). The same authors also observed that there was no difference in seminal volume in different seasons in Brazil.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The mean of seminal volume of the Pantaneiro stallions was similar to the mean(44,4 ± 27,9) observed by Rua et al (2016). The same authors also observed that there was no difference in seminal volume in different seasons in Brazil.…”
Section: Discussionsupporting
confidence: 82%
“…The sperm concentration observed in this study is lower than observed in others (Waheed et al, 2013;Rua et al, 2016). We could consider the difference between breeds the main cause, because the climates among studies are similar according to temperature, with high temperatures during the entire year.…”
Section: Discussioncontrasting
confidence: 63%
“…O volume de sêmen filtrado encontrado (de 42±21,1 a 55,4±15,7mL) está entre os padrões desejáveis pelo Colégio Brasileiro de Reprodução Animal (Manual..., 2013), que variam de 40 a 60mL, e de acordo com os valores demonstrados por Rua et al (2016), que também trabalharam com a raça Mangalarga Marchador, no estado do Rio de Janeiro, Brasil, e obtiveram volume de 44,4±27,9mL.…”
Section: Resultsunclassified
“…Entretanto, em estudos realizados no hemisfério sul, por Rua et al (2016), foram relatadas diferenças dos valores de concentração espermática entre a estação reprodutiva (507±615,9) e fora da estação (278±224,9). Diferentemente, Freitas (2010), quando trabalhou com cavalos da raça Mangalarga Marchador, obteve maior média de concentração espermática no outono: 311,8±148,3 e no inverno: 358,7±180,6 do que na primavera: 178,9±97,0 e no verão: 191,0±110,1, fato que não foi observado no presente estudo.…”
Section: Resultsunclassified